2016
DOI: 10.1021/acs.analchem.6b02762
|View full text |Cite
|
Sign up to set email alerts
|

All-Solid-State Reference Electrode with Heterogeneous Membrane

Abstract: Novel reference electrodes with a solid contact coated by a heterogeneous polymer membrane are described. The electrodes are obtained using Ag nanoparticles, AgBr, KBr suspended in tetrahydrofuran solution of PVC and DOS and deposited on Ag substrate, or another substrate covered with Ag, by drop casting. After a short period of soaking in a KBr solution, stable and reproducible formal potentials of -157 ± 2 mV (vs Ag/AgCl/3 M KCl) were observed, and the solid-contact reference electrodes were ready to use. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…Another idea was used Co(II)/Co(III) complexes with 1,10‐phenanthroline as the material for RE . Another example is the all‐solid‐state reference electrode with heterogeneous membrane, which was made using silver nanoparticles . One of the most interesting ideas, which has a large potential application is the use of Ag/AgCl electrode dipped in a KCl dispersed in the polymer .…”
Section: Introductionmentioning
confidence: 99%
“…Another idea was used Co(II)/Co(III) complexes with 1,10‐phenanthroline as the material for RE . Another example is the all‐solid‐state reference electrode with heterogeneous membrane, which was made using silver nanoparticles . One of the most interesting ideas, which has a large potential application is the use of Ag/AgCl electrode dipped in a KCl dispersed in the polymer .…”
Section: Introductionmentioning
confidence: 99%
“…PVC is the most frequently used polymer for solid-contact ion-selective plastic membrane sensors. Moreover, PVC can also be used for designing solid contact reference electrodes by drop-casting, as has recently been shown [ 22 , 23 ]. Our group has contributed to meeting the above challenge by reporting on the 3D printing fabrication of a PVC solid-contact reference electrode (SC REF 3D) [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was demonstrated that the PVC heterogenous membranes with silver bromide-KBr salts work superbly as the all-solid-state reference electrodes [73] and that both KBr-and KCl-containing reference membranes are excellent internal solid contact for ion-selective electrodes [74].…”
Section: Introductionmentioning
confidence: 99%
“…These reports provide the signal of a breakthrough in the reference electrode technology which may be called "heterogenous membrane revolution" [73,74]. Material-wise, two aspects of novelty are striking: (1) the application of inorganic salts, and (2) new inert binders which constitute a composite membrane and mechanically processable membranes suitable for electrochemical measurements.…”
Section: Introductionmentioning
confidence: 99%